The Existence of Moments of k-Class Estimators - Kinal, Terrence W. (Econometrica, 1980)
For the regression equation C = A,B + e where A is a p x q stochastic matrix whose elements are independently distributed and contemporaneously correlated with the elements of 8, the lth moment of the least squares estimator of (3 exists if and only if l < p - q + 1. In particular, this implies that the lth moment of the k-class estimator of the coefficients of the G1 -1 non-normalizing endogenous variables of an equation with K1 included and K2 excluded exogenous variables in a simultaneous system with N observations exists if and only if 1 < M where